PTBP1 Targets ILK to Regulate the Hypoxia-Induced Phenotypic Transformation of Pulmonary Artery Smooth Muscle Cells - Yan G; Sun R; Chen Z; Pan X; Sheng Z; Tang C (Dove Medical Press, 2021)
Gaoliang Yan, Renhua Sun, Zhongpu Chen, Xiaodong Pan, Zulong Sheng, Chengchun Tang Department of Cardiology, Zhongda Hospital of Southeast University Medical School, Nanjing, 210009, People’s Republic of ChinaCorrespondence: Gaoliang YanDepartment of Cardiology, Zhongda Hospital of Southeast University Medical School, Nanjing, 210009, People’s Republic of ChinaTel +86 18761890380Email yangaol@hotmail.comPurpose: Pulmonary hypertension (PH) is a pathological process mainly characterized by the progressive increase in pulmonary vascular resistance. The degradation of pulmonary artery smooth muscle cells (PASMCs) from contractile/differentiated phenotype to synthetic/dedifferentiated phenotype is a key factor for hypoxic pulmonary hypertension.Materials and Methods: In this study, qPCR was performed to evaluate the gene expression of mRNAs. Western blot, immunofluorescence and RNA pull down were used to detect gene expression levels.Results: We found that the gene expression of polypyrimidine tract-binding protein1 (PTBP1) was increased significantly in a time-dependent manner in rats PA tissues and PASMCs after hypoxia. PTBP1 knockdown can inhibit the phenotypic transition of PASMCs. PTBP1 inhibits the phenotypic transition of PASMCs. In addition, PTBP1 inhibits the integrin-linked kinase (ILK) expression under hypoxic conditions, thereby down-regulating the expression of downstream proteins. It inhibits the phenotypic transition of PASMCs and alleviates pulmonary hypertension.Conclusion: In conclusion, PTBP1/ILK axis promotes the development of PH via inducing phenotypic transition of PASMCs. This may provide a novel therapy for PH.Keywords: pulmonary hypertension, polypyrimidine tract-binding protein 1, integrin-linked kinase, pulmonary artery smooth muscle cells